Irisin is associated with osteoporotic fractures independently of bone mineral density, body composition or daily physical activity. (6th January 2015) - Palermo, Andrea; Strollo, Rocky; Maddaloni, Ernesto; Tuccinardi, Dario; D'Onofrio, Luca; Briganti, Silvia Irina; Defeudis, Giuseppe; De Pascalis, Mariangela; Lazzaro, Maria Concetta; Colleluori, Georgia; Manfrini, Silvia; Pozzilli, Paolo; et al.
Summary Background Although there is an evidence of correlation between irisin and osteoporotic fractures, previous studies have not elucidated the relationship between irisin and either lean or fat mass. The main aim of this study is to investigate the relationship between irisin and body composition in postmenopausal women with osteoporosis and the impact of irisin levels on fragility vertebral fractures. Methods In this cross‐sectional study, 36 overweight subjects affected by at least one vertebral osteoporotic fracture confirmed by an X‐ray vertebral morphometry and 36 overweight nonosteoporotic subjects were enrolled. Serum irisin levels were measured using an irisin competitive ELISA. We evaluated lumbar spine and hip BMD and body composition using dual energy X‐ray absorptiometry. To measure and monitor daily physical activity, each subject wore an armband for approximately 72 h. Results No significant correlations were found between irisin and BMD at any site and between irisin with either lean or fat mass. Serum levels of irisin were not correlated with the daily physical activity. Serum irisin levels were lower in subjects with previous osteoporotic fractures than in controls (P = 0·032), and the difference in irisin levels remained significant after adjustment for creatinine (P = 0·037), vitamin D (P = 0·046), lean mass (P = 0·02), lumbar BMD (P = 0·023) and femoral BMD (P = 0·032). Conclusion Our data confirm an inverse correlation between irisin levels and vertebral fragility fractures, but no significant correlation was found with BMD or lean mass. Irisin may play a protective role on bone health independent of BMD but further studies are needed to clarify the relationship between irisin and bone metabolism.